Cardiac structure and function before and after bariatric surgery: a clinical overview. Issue 6 (12th September 2018) - Lascaris, B.; Pouwels, S.; Houthuizen, P.; Dekker, L. R.; Nienhuijs, S. W.; Bouwman, R. A.; Buise, M. P.
Summary: Obesity, defined as a body mass index of ≥30 kg/m 2, is the most common chronic metabolic disease worldwide and its prevalence has been strongly increasing. Obesity has deleterious effects on cardiac function. The purpose of this review is to evaluate the effects of obesity and excessive weight loss due to bariatric surgery on cardiac function, structural changes and haemodynamic responses of both the left and right ventricle.